THE ESSENCE OF INTEGRATED BUSINESS APPLICATION COURSE TO ENHANCE STUDENTS’ ENTREPRENEURIAL SKILLS - Claudius Bona (Jurnal Bisnis Terapan, 2017)
People talk about entrepreneurship simply everywhere. This trend also happens in Indonesia as it is proved with the increase of 3.1% entrepereneurship development ratio in 2016 (www.depkop.go.id). The hype is supported by the expansion of e-commerce in Indonesia. The rise of e-commerce entrepreneurs in Indonesia is one of the factors that makes Business English study program to set up Integrated Business Applications (IBA) course. The course is intended to make students learn to do business activities by doing real online business. This research would like to reveal whether the IBA course could enhance students’ entrepreneurial skills or not. This research uses fifth semester students who already passed this course as respondents. The findings of this research reveal that Integrated Business Applications course is really essential to enhance students’ entrepreneurial skills. Further research could be implemented in order to find the impact of this course to the other study program.